The effects of a brief intervention at home based on shared reading to promote children’s oral language - Camila Domeniconi; Marta Gràcia; Priscila Benitez (CoDAS)
ABSTRACT Purpose The general aim of the present study was to analyse eight mother-child interactions during shared reading with children and to assess the efficacy of a brief intervention with the mothers to promote changes in the strategies they used to develop their children’s oral language. The specific objectives were to work collaboratively with mothers, to analyse the interactions between mothers and their children before and at the end of the intervention period. Methods Mothers participated in five meetings to reflect collaboratively on strategies to promote improvements in communicative interactions in a family context and in children’s oral language and during the shared reading episodes. Standardized language tests were used to assess the oral language of children who were five and six years old and typically developing. Results The results showed that all children improved some aspects of their communicative repertoire in standardized tests and/or in the observations of natural or structured situations. Conclusion We conclude that the use of strategies such as a brief intervention to promote communicative interactions between mothers and their children may have contributed to promoting children’s oral language.